Community Based Natural Resource Management in Chopan Block of District Sonbhadra, U.P.: An Appraisal - Singh, Shyam B.; Juyal, R.; Singh, Suman (National Geographical Journal of India, 2022)
A major section of the Indian poor live in the villages directly depending upon the natural resources and ecological support system for their livelihoods. Over 60 percent of the country’s workforce directly depends on agriculture, fisheries and forests and the dependency of the poor on natural resources is more as compared to others. Increase in biotic pressure has lead to the over-exploitation and degradation of natural resources. The availability of natural resources to rural communities and especially to the poor has decreased severely. The paucity of resources also leads to internal conflict giving opportunity to outsiders to exploit the situation. The government machinery has proved to be ineffective in maintaining the traditional balance. Now there is a felt need for a decentralized approach for natural resource management which has to be implemented at district and block levels. The present paper assesses the scope for community based natural resource management (CBNRM) in Chopan Block of Sonbhadra District, U.P.